SINERGITAS AKTOR DALAM PENGEMBANGAN DESA WISATA OKURA DI KELURAHAN TEBING TINGGI OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - ", Rakamdani; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Okura Tourism Village, which the government professes as one of the tourist attractions in the ordinary city, has been moved to develop the government's locality tourism village. The purpose of this study was to find out the synergy of actors in the development of Okura Tourism Village in Tebing Tinggi Okura Village, Rumbai Pesisir Subdistrict, Pekanbaru City and to find out the factors that inhibited it, the theory used was Najiati theory, namely two indicators in synergy namely Communication and Coordination. The method of study used is a qualitative form of research that accommodates both primary and necessary case studies and data through interview, observation, and documentation technique. The results showed that while mutual activism among actors is already underway, state cultural and tourism agencies and tourism officials have recently been the best because they have not made relatively rare visits. Limiting factors are facilities and infrastructure, human resources, and budget. The findings suggest that actors' manners in the development of the Okura Tourism Village come more frequently and interact regularly to cooperate in the development of the Okura Tourism Village, provide volunteer service and training while providing tools and training. a person in the tourist town of Okura. * Keywords : Synergy, Actors, Tourism Development and Tourism Village